Some results on ? - statistical convergence on time scales - Altin, Yavuz (Maejo Univ, 2017)
Some sets of sequences on a time scale are introduced by considering the various sequences mu(triangle lambda(t)) and mu(triangle beta(t)) in the class.. Furthermore, some inclusion results on these sets are obtained.
Keywords: statistical convergence; sequence spaces; time scales